Obesity and polycystic ovary syndrome - Vrbikova, Jana; Hainer, Vojtech (Obesity facts, 2009)
Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies in women of fertile age. Obesity is encountered in 30-70% of PCOS-affected women, and its presence significantly modifies both clinical and laboratory expression of the syndrome. Obesity increases the risk of co-morbidities associated with PCOS, such as impaired glucose tolerance and type 2 diabetes mellitus, hyperlipidemia and arterial hypertension. The etiopathogenesis of obesity in PCOS has not yet been exactly clarified. There clearly is a vicious circle of abdominal obesity, insulin resistance, and hyperadrogenemia. Differences in ghrelin and neuropeptide Y levels between PCOS patients and those with simple obesity were also described. Weight loss is the first choice recommendation for the treatment of clinical manifestations of PCOS, such as menstrual cycle irregularities, infertility or hirsutism. However, the best treatment approach in obese PCOS patients remains to be defined. Studies concerning different weight loss regimens, antiobesity drugs, bariatric surgery, insulin sensitizers, and hormonal therapy are reviewed.
Keywords: deprese; Diabetes Mellitus, Type 2; Polycystic Ovary Syndrome; Depression; Weight Loss; hmotnostní úbytek; obezita; diabetes mellitus 2. typu; lidé; Insulin Resistance; Humans; porucha glukózové tolerance; Hypertension; Hyperlipidemias; hypertenze; inzulinová rezistence; rizikové faktory; Glucose Intolerance; Hyperandrogenism; Obesity; hyperlipidemie; ženské pohlaví; syndrom polycystických ovarií; hyperandrogenismus; Female; Risk Factors